Theory of plastic mechanism control for seismic design of steel plate shear walls. (15th May 2021) - Bahrami Zadeh, Hojjat; Mahjoub, Reza; Raftari, Mehdi; Fathi Sepahvand, Mostafa
Highlights: Seismic design of the steel plate shear wall with rigid beam-column connections. The theory of plastic mechanism control is proposed with reference to SPSW. Presenting an accurate design procedure to achieve the global mechanism. Seismic performance of the designed SPSWs using the nonlinear static analyses. Abstract: The present study deals with the seismic design of steel plate shear walls (SPSWs) using the theory of plastic mechanism control (TPMC). The TPMC is based on the theory of kinematic rigid-plastic, which by applying the second-order effects, can prevent the development of undesirable generic mechanisms such as soft stories, and it can ensure that the structure reaches the global mechanism. The global mechanism is a mechanism in which the damage distribution is uniform, and therefore, the maximum energy dissipation in the structure can be fulfilled. The present study first presents the seismic design provisions of the SPSW and then the SPSW design algorithm using TPMC. For practical examples, three frames including three-, six-, and nine-story frames with SPSW were designed using the proposed algorithm. For validation of the design procedure, the designed frames were evaluated by means of non-linear static analysis, showing that the frames can reach the global mechanism and their excellent seismic performance.